Aging Fly Cell Atlas identifies exhaustive aging features at cellular resolution. - Lu, T.C.; Brbi?, M.; Park, Y.J.; Jackson, T.; Chen, J.; Kolluru, S.S.; Qi, Y.; Katheder, N.S.; Cai, X.T.; Lee, S.; Chen, Y.C.; Auld, N.; et al. (Science, 2023)
Aging is characterized by a decline in tissue function, but the underlying changes at cellular resolution across the organism remain unclear. Here, we present the Aging Fly Cell Atlas, a single-nucleus transcriptomic map of the whole aging Drosophila. We characterized 163 distinct cell types and performed an in-depth analysis of changes in tissue cell composition, gene expression, and cell identities. We further developed aging clock models to predict fly age and show that ribosomal gene expression is a conserved predictive factor for age. Combining all aging features, we find distinctive cell type-specific aging patterns. This atlas provides a valuable resource for studying fundamental principles of aging in complex organisms.